Sustainable Public Hiring: An Analysis of the Profile of Procurement Conduced by Brazilian Public Institutions - Souza, Talita Ferreira de; Quelhas, Osvaldo Luiz Gonçalves; Gomes, Carlos Francisco Simões (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This article, exploratory and descriptive, aims to examine scientific production about sustainable public hiring and to outline a profile of the “green” procurements processes used by Brazilian public administration. The research looked for data contained at the Government Procurement website – COMPRASNET, which comprises a total of 2.291 sustainable items bid by different Procurement Management Units. From items bid, an analysis was conducted to identify which Brazilian regions and states contributed the most for the sustainable public procurement policy and what kinds of good are more common in the bidding help by government agencies. Additionally, this study used descriptive statistics for analyzing data and aimed to contribute to the scientific production about a contemporary theme.